SEISMOLOGICAL EVIDENCE FOR CRUSTAL-SCALE THRUSTING IN THE ZAGROS MOUNTAIN BELT (IRAN) - Paul A.; Kaviani A.; Hatzfeld D.; Mokhtari M.; Vergne J. (My University, 2006)
Crustal receiver functions (RFs) computed from the records of 45 temporary seismological stations installed on a 620-km-long profile across central Zagros provide the first direct evidence for crustal thickening in this mountain belt. Due to a rather short 14 km average station spacing, the migrated section computed from radial RFs displays the Moho depth variations across the belt with good spatial resolution. From the coast of the Persian Gulf to 25 km southwest of the Main Zagros Thrust (MZT), the Moho is almost horizontal with slight depth variations around 45 km. Crustal thickness then increases abruptly to a maximum of ~70 km beneath the Sanandaj-Sirjan metamorphic zone, between 50 and 90 km northeast of the surface exposure of the MZT. Further northeast, the Moho depth decreases to ~42 km beneath the Urumieh-Dokhtar magmatic assemblage and the southern part of the Central Iranian microcontinent. The region of thickest crust is located ~75 km to the northeast of the Bouguer anomaly low at -220 mGals. Gravity modelling shows that the measured Moho depth variations can be reconciled with gravity observations by assuming that the crust of Zagros underthrusts the crust of central Iran along the MZT considered as a crustal-scale structure. This hypothesis is compatible with shortening estimates by balanced cross-sections of the Zagros folded belt, as well as with structural and petrological studies of the metamorphic Sanandaj-Sirjan zone. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CRUSTAL STRUCTURE; IRAN; MOUNTAIN BELT; RECEIVER FUNCTIONS; ZAGROS